Monoamine and genome-wide DNA methylation investigation in behavioral addiction - Asaoka, Yui; Won, Moojun; Morita, Tomonari; Ishikawa, Emi; Lee, Young-A; Goto, Yukiori (Scientific reports, 2020)
Behavioral addiction (BA) is characterized by repeated, impulsive and compulsive seeking of specific behaviors, even with consequent negative outcomes. In drug addiction, alterations in biological mechanisms, such as monoamines and epigenetic processes, have been suggested, whereas whether such mechanisms are also altered in BA remains unknown. In this preliminary study with a small sample size, we investigated monoamine concentrations and genome-wide DNA methylation in blood samples from BA patients and control (CT) subjects. Higher dopamine (DA) metabolites and the ratio between DA and its metabolites were observed in the BA group than in the CT group, suggesting increased DA turnover in BA. In the methylation assay, 186 hyper- or hypomethylated CpGs were identified in the BA group compared to the CT group, of which 64 CpGs were further identified to correlate with methylation status in brain tissues with database search. Genes identified with hyper- or hypomethylation were not directly associated with DA transmission, but with cell membrane trafficking and the immune system. Some of the genes were also associated with psychiatric disorders, such as drug addiction, schizophrenia, and autism spectrum disorder. These results suggest that BA may involve alterations in epigenetic regulation of the genes associated with synaptic transmission, including that of monoamines, and neurodevelopment.